Making Ends Meet : The Way of the Prince Edward Island Fisherman’s Wife - Reddin, J. Estelle (Ethnologies, 1991)
For the fîsherman’s wife the problem of making ends meet is cast in a cyclical time frame, tied to the ends of the seasons of the year and the seasons of fishing. Added to the problem is the risk and uncertainty prévalent in the occupation of fishing. Making ends meet involves distinctive ways of subsistence provisioning rather than total dependence on cash income; and, as well, adaptation to the technology and economy of mainstream culture. This article describes the strategies for making ends meet used by a sample of Prince Edward Island women, wives of bona fide fishermen.